Characterization of Riemerella anatipestifer Strains Isolated from Various Poultry Species in Poland - Anna Nowaczek; Marta Dec; Dagmara Stępień-Pyśniak; Jarosław Wilczyński; Renata Urban-Chmiel (Antibiotics, 2023)
Riemerella anatipestifer (R. anatipestifer) is one of the common pathogens found in poultry flocks, resulting in serious economic losses for the poultry industry due to high mortality, reduced growth rate, poor feed conversion, increased condemnations, and high treatment costs. The aim of this study was to phenotypically characterize phylogenetic relationships and assess the presence of resistance gene strains of R. anatipestifer obtained from various poultry species in Poland. A total of 57 isolates of Riemerella were included in this study. A polymerase chain reaction (PCR) and matrix assisted laser desorption ionization mass spectrometry (MALDI-TOF MS) were used for identification of the strains. The phylogenetic relationship of the R. anatipestifer isolates was determined by analysing the rpoB gene sequence. The susceptibility to antibiotics was evaluated by minimum inhibitory concentration (MIC) in liquid media. All of the field strains of R. anatipestifer were grouped into one of two clades resulting from rpoB gene sequencing. High MIC50 and MIC90 values were obtained for gentamycin, amikacin, and colistin. Low MIC50 and MIC90 values were obtained for amoxicillin cefuroxime, cefoperazone, piperacillin, and trimethoprim/sulfamethoxazole. Among the resistance genes, tet(X) and ermF were identified most frequently. This is the first phenotypic characterization of R. anatipestifer strains obtained from poultry flocks in Poland.